Impact of transcatheter aortic valve implantation on left atrial appendage flow velocities. Issue 6 (15th February 2016) - Ando, Tomo; Holmes, Anthony A.; Slovut, David P.; Taub, Cynthia C.
ABSTRACT: Purpose: Left atrial appendage (LAA) flow velocity has not been extensively studied in patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI). The aim of this study was to assess the impact of TAVI on LAA flow velocity. Methods: Medical records of consecutive TAVI recipients were reviewed retrospectively. Patients with persistent atrial fibrillation were excluded. LAA velocities were measured before and after TAVI by transesophageal echocardiography. Results: Sixty‐one patients were included. Mean LAA emptying (EV) and filling (FV) flow velocity before TAVI were 33 ± 16 cm/s and 31 ± 14 cm/s, respectively. They increased to 37 ± 20 ( p = 0.0036) and 33 ± 13 cm/s ( p = 0.047) after TAVI in the whole population sample, but not in patients with normal flow AS. In low‐flow, low‐gradient (LFLG) AS patients, EV and FV increased from 36 ± 22 to 47 ± 30 cm/s ( p < 0.01), and from 29 ± 12 to 40 ± 15 cm/s ( p < 0.01), respectively, after TAVI. There was no difference between normal flow and LFLG AS patients in the number of patients who achieved EV ≥ 40 cm/s post‐TAVI (35% versus 47%, p = 0.54, respectively). Conclusions: LAA EV and FV were low prior to TAVI and increased significantly after TAVI only in patients with LFLG AS. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :375–382, 2016